The (in)visibility of Moriscos in the baptismal records of New Castile (1570-1610) - Moreno Díaz del Campo, Francisco J. (2018)
Parish records are one of the most important sources to study Morisco minority, mainly in relation to their demography and religious practice. To a large extent, this is possible because the Moriscos were explicitly identified in the baptism, marriage and death certificates. However, and unfortunately, this situation did not always occur, giving rise to an apparent disappearance of them in the documentation. This paper analyses which were the identification formulas used by the Castilian parish priests when they registrered Moriscos' baptisms. Reasons that can explain the disappearance of many of Moriscos in that documentation are analysed too.